Economic Social Factor of Farmer and the Affect to Paddy Field Farming Productivity in Sungai Penuh City-Indonesian - Saidin Nainggolan; Yanuar Fitri; Nur Fitri Ani (RIRAI Publisher, 2021)
The research aims to analyze economic social factor of farmer and the affect to paddy field farming productivity. Location determination do as purposive. Total of sample farmers are 62 farmers. Data analysis uses primary data and uses approach with Partial Least Square (PLS). Match test of outer model is convergent validity test, discriminant validity and composite validity are qualify. Inner model test has value of Q2 amount of 99,3% meets match test of inner model. The affect of social factor and economic directly have coefficient amount of -0,043 and 0,038 to paddy field farming productivity with p value (0,046)<α(0,05) and p value (0,033)<α(0,05). The affect of social factor indirectly through of production input variable usage and activeness of farmer group have coefficients amount of 0,237 and 0,034 to productivity with p value (0,059)>α(0,05) and p value (0,026)<α (0,05). Economic factor through input production variable usage and activeness of farmer group have coefficients amount of 0,367 and 0,010 to productivity with p value (0,000)<α (0,05) and p value (0,099)>α(0,05). Total affect of the research of social factor and economic have coefficients amount of 0,228 and 0,415 to paddy field farming productivity with p value (0,064)>α(0,05) and p value (0,000)<α(0,05). The relation to this in order to empower farmer to raise of paddy field farming productivity need to pay attention of social factor, economic factor, cultivation technology of paddy field farming.